FEATURES OF SIBERIAN POLICE BUREAUCRACY IN THE PERIOD OF REFORMS IN THE XIX CENTURY - I. A. Konovalov (Гуманитарные и юридические исследования)
Based on pre-revolutionary legislation the article comprehensively considers the process of Siberian police bureaucracy development. The growing interest in the history of local government connected not only with the aspiration of historians to look more deeply into the past but also with practical needs. Researching of the forgotten traditions of public administration allows to take greater account of historical experience that has been accumulated over the centuries. We also need to take a look at already known facts and events in the light of today's realities. This approach may overcome the old myths and misconceptions and also prevent the birth of new ones. Theoretical and methodological basis of the research were such principles of historical knowledge as objectivity, historicism, alternativeness and social approach which are assuming an unbiased approach to the analysis of the researched problems, as well as a critical attitude to sources. The author concludes that the powers of the administrative and police authorities in the region had their own features and were much wider than in the central provinces of the Russian Em- pire. Moreover, the absence of the nobility and noble self-government exempted police officers from control by noble corporate organization. Other features of the region were its peripheral status and role of hard labor. A characteristic feature of the Siberian administration was its militarized organization. Siberian administrators had poor theoretical training, and often they did not even have any systematic education. This lowered the professional level of the employees of the Siberian administrative police bodies. A vast territory, underdeveloped communications and weak intensity of socio-economic and political ties generated uncontrolled autonomy in the actions of local police bodies, which were poorly provided with an appropriate legal base. The remoteness and huge size of Siberia generated unheard-of arbitrariness from the local police bureaucracy. The history of the Siberian local management in the XIX century is an almost continuous series of service abuses.